Enzymatic conversion of pretreated lignocellulosic biomass: A review on influence of structural changes of lignin. (March 2021) - Sheng, Yequan; Lam, Su Shiung; Wu, Yingji; Ge, Shengbo; Wu, Jinglei; Cai, Liping; Huang, Zhenhua; Le, Quyet Van; Sonne, Christian; Xia, Changlei
Graphical abstract: Highlights: Different methods to analyze lignin structure are reviewed. Structural changes of lignin is compared in various pretreatments. Lignin properties are strongly related to efficiency of enzymatic conversion. In-situ strategies of lignin structural modification enhance enzymatic hydrolysis. The formation of pseudo-lignin and its inhibition to enzymatic hydrolysis. Abstract: The demands of energy sustainability drive efforts to bio-chemical conversion of biomass into biofuels through pretreatment, enzymatic hydrolysis, and microbial fermentation. Pretreatment leads to significant structural changes of the complex lignin polymer that affect yield and productivity of the enzymatic conversion of lignocellulosic biomass. Structural changes of lignin after pretreatment include functional groups, inter unit linkages and compositions. These changes influence non-productive adsorption of enzyme on lignin through hydrophobic interaction and electrostatic interaction as well as hydrogen bonding. This paper reviews the relationships between structural changes of lignin and enzymatic hydrolysis of pretreated lignocellulosic biomass. The formation of pseudo-lignin during dilute acid pretreatment is revealed, and their negative effect on enzymatic hydrolysis is discussed.